PROFIL KEHIDUPAN ANAK SEBAGAI PENGEMIS DI KAWASAN SIMPANG EMPAT PASAR PAGI ARENGKA KECAMATAN TAMPAN KOTA PEKANBARU - Sari, Fatmala; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was carried out in the Simpang Empat Area, Arengka Morning Market, Handsome District. The purpose of this study was to determine the profile of socio culture life of children who work as beggars in the Simpang Empat Lampu Merah area of the Arengka Morning Market, Handsome District. The focus of this research is the social impact of children who as beggars in the Simpang Empat area of the Arengka Morning Market, Handsome District. The technique of determining samples by purposive sampling and determining the number of samples as many as 4 people. The author uses qualitative descriptive methods and data instruments are observation, interviews and documentation. The study found that the social and economy conditions of child laborers as scavengers in the Handsome District of Pekanbaru City are as follows: Circumstances of Beggar Families of Children, From the research conducted it was known that children who work as beggars come from disadvantaged families. Beggars Association Children, most of the children who work as beggars, are children who are ostracized from their peers, because they think that the children who work as beggars are poor people, so they feel it is inappropriate to be friends with him. The Environment of Child Labor Residence, The recognition given by the child who worked as a beggar interviewed found that most of them lived in very simple homes. Keywords: Social Economy, Children, Beggars